Effectiveness of 0.05% Cyclosporine versus Standard Treatment of Vernal Kerato-Conjunctivitis (VKC) in Young Patients: Doi: 10.36351/pjo.v40i4.1911 - Ramsha Jehangir; Humera Zafar Ali; Parvez, Ayesha; Farooq, Amna; Mushafia Hassan (Pakistan Journal of Ophthalmology, 2024)
Purpose: To compare the effectiveness of 0.05% cyclosporine eye drops versus standard treatment in patients of moderate to severe vernal kerato-conjunctivitis (VKC). Study Design: Quasi experimental study. Place and Duration of Study: Institute of Ophthalmology, Eye Unit-1, King Edward Medical University, Mayo Hospital, Lahore from June to December 2019. Methods: This study includes 104 patients (age 5-16 years), with VKC. Patients were divided into two groups. Group A was given standard treatment for moderate to severe VKC, which included topical corticosteroids (FML 0.1% eye drops) QID, in addition to antihistamines and mast cell stabilizers (Olopat D 0.2% eye drops) QIDand group B was given 0.05% Cyclosporine A(CyS-A) eye drops QID.The frequency of mild, moderate, and severe disease was determined for each group. Data was analyzed and independent sample t-test was applied. P value of < 0.05 was taken as significant. Results: There were 60 males and 44 female patients. The mean age in Group A was 9.34 ± 2.09 years and in group B was 9.36 ± 2.71 years. There was significant difference in mean clinical symptoms and sign score between group A and group B (p <0.001) at 3 months, suggesting that topical 0.05% cyclosporine is more effective as compared to standard therapy in moderate to severe VKC. Conclusion: 0.05% cyclosporine eye drops are effective in treating moderate to severe VKC in terms of reduction of clinical manifestations of disease.